HUBUNGAN SIKAP KERJA DENGAN KELUHAN MUSCULOSKELETAL PADA PENYORTIR TEMBAKAU DI GUDANG SORTASI TEMBAKAU KEBUN KLUMPANG SUTK PTPN II TAHUN 2015 - friska yuni utari; kalsum *; eka lestari mahyuni (Lingkungan dan Kesehatan Kerja, 2015)
ABSTRACT The activity of tobacco sorter with unergonomics work posture have some risks to cause musculoskeletal disorders. Musculoskeletal disorders are disorders on joints, ligaments and tendons that caused by static load receives on muscle repetitive and continuously in long periods of time. The research was survey analitic with cross sectional design that aims to find out the correlation of work posture to musculoskeletal disorder in tobacco sorter at Tobacco Storeroom Kebun Klumpang SUTK PTPN II. Sample of this study was 30 workers of tobacco sorter (total population). The data of work posture were gathered with REBA (Rapid Entire Body Assessment) method and Nordic Body Map questionnaire to assess the level of musculoskeletal complaints. The data analyzed using Chi Square statistic test. The result of the study showed that worker in low category of musculoskeletal complaints was 10 workers (33,3%) and 20 workers (66,7%) was in medium category. The biggest number of musculoskeletal complaint in pain was in the back 83,3%. The other was in waist, buttocks, legs, lower neck, shoulders, and thighs. The biggest number of musculoskeletal complaint in very pain was in legs 16,7%. The other was in waist, thighs,buttocks, ankles, foots, upper arm, and knees. The result of work posture assessment with REBA method showed that worker with low level risk of work posture was 8 workers (26,7%) and the worker with medium level risk was 22 workers (73,3%). The result of Chi Square statistic test showed that there were significant relation between work posture with musculoskeletal complaint at p value 0,007 which was p < 0,05. Thus, work posture had relation with the occurrence of musculoskeletal disorders in tobacco sorter. It is recommended for the worker to work with sitting erect posture, interspersed with bent slightly.